PELATIHAN, PENILAIAN KINERJA, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI (STUDI KASUS PERUSAHAAN UMUM DAERAH) - Bintang Balele; Hariyanti Hariyanti; Kustiany Kustiany (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2022)
This study aims to analyze the relationship between training, performance appraisal, and competence on employee performance at the Regional Drinking Water Company (PERUMDA) in Maros Regency. This research is a consensus research in which all the population used as respondents, which are 57 employees. Based on statistical results, the study found that training and performance appraisal affects positively and significantly employee performance. Differently, the study did not find the relationship between competence on employee performance. This suggest that competence based on education, with the exception of training and coaching, did not drive up the employee performance.